(untitled) - Bali, N. (Hingham, Massachusetts, 2007)
This book has hundreds of examples with in-text solution. Interm of content, it covers the entire sequence of mathematical topics need by the majority of university program, including geometry, matrices integrals, ODE, PDE, vector calculus complex variable, probolity statistics numerical methods and more.
Keywords: Engineering mathematics,Toán kỹ thuật; Data processing,Xử lý dữ liệu